O PIBID e o engajamento acadêmico: perspectivas em um curso de licenciatura em química - Santos, Aline Izaiane Farias dos (2023)
This research has as its centrality the academic engagement provided by the Institutional Program of Scholarships for Teaching Initiation (PIBID), a program that aims to encourage scholarship holders to know and participate in the reality of a public school of Basic Education, so that they are known the professional dimensions, as well as the concrete possibilities of exercising teaching, providing the development of new teaching methodologies. Thus, the present work proposes to understand how the student's permanence in the program can generate academic engagement, in order to understand what are the bases that sustain the engagement, as well as its relationship with PIBID. The methodological course involved the analysis of questionnaires and interviews, since the research has a qualitative nature, of an exploratory nature, which aims to carry out deeper analyzes and interpretations by providing a more detailed analysis of attitudes, investigations and behavioral trends of graduates of the PIBID. The research has as collaborators students of a Degree in Chemistry, who were PIBID scholarship holders at the Federal Institute of Education, Science and Technology Baiano (IF Baiano), Catu-BA campus. Seeking to know which forms of academic engagement were built thanks to participation in this Program. The first questionnaire aimed to get to know the academic life of PIBID's egress participants; the second turned to issues related to the course, experiences at PIBID, and socioeconomic issues. The questionnaires, used in an undergraduate research that investigated the Program, were validated and adapted according to the objectives listed here. The semi-structured interview was analyzed based on the categorization of engagement extracted from the theoretical framework. The content analysis carried out sought to bring reflections on academic engagement. Based on the theoretical framework raised and on the research carried out, the categories of engagement found were: "time in which the student dedicated himself to carrying out tasks", "quality of the student's diligence", "student involvement with the studies", "results of learning", "good practices in Higher Education Education", "integration of the social with the academy" which, unified, provided "academic engagement". : “experience as a scholarship holder”, “learning for teaching”, “knowledge construction”, “school structure as a possibility of development”, “importance of participating in scientific events”. conclusion that the graduates were challenged to develop the activities proposed from their participation in PIBID, which promoted an engagement. Starting from the assumption that academic engagement is not something palpable, but perceptible within the speeches of the graduates, the present work attested that participation in PIBID enabled the process of academic engagement to be initiated and continued, and that the level of academic engagement depends on several internal and external factors, not being able to measure it, but being noticeable that it occurred among the participants of this search.